AN ANTIHERO'S JOURNEY: THE POLITICAL CAMPAIGN OF JAIR BOLSONARO AND THE USE OF ARCHETYPES ON FACEBOOK. - Beira Machado, Vitor Matheus; Chapaval Pimentel, Pedro; Slongo Garcia, Bruno Eduardo (Journal for the Study of Religions & Ideologies)
In Brazil, the shift from the traditional media vehicles to an "electronic podium" has provided more flexibility in terms of time, costs, and language for candidates to elaborate their electoral campaigns. Given the extensive use of and the importance given to Facebook during Jair Bolsonaro's campaign, this article assesses how the candidate depicted his image on his Fan Page. Drawing on the literature on political and electoral communication and brand archetypes, and based on a sample of 158 posts made by Bolsonaro's Facebook Fan Page/jairmessias.bolsonaro between August and October 2018, it is argued that Bolsonaro's marketing strategy developed a combination of two rival archetypes: the antihero. The study contributes to the literature on political brands showing that a narrative build simultaneously on a mythical/heroic and an outlaw favored the candidate in a context of political polarization.